History in the comic mode: medieval communities and the matter of person - Fulton, Rachel; Holsinger, Bruce (Columbia Univ. Press, 2007)
Forgetting Hathumoda : the afterlife of the first abbess of Gandersheim / Frederick S. Paxton -- "If one member glories-- " : community between the living and the saintly dead in Bernard of Clairvaux's Sermons for the Feast of All Saints / Anna Harrison -- The pope's shrunken head : the apocalyptic visions of Robert of Uzès / Raymond Clemens -- Thomas of Cantimpré and female sanctity / John Coakley -- The changing fortunes of Angela of Foligno, daughter, mother, and wife / Catherine M. Mooney -- "A particular light of understanding" : Margaret of Cortona, the Franciscans, and a Cortonese cleric / Mary Harvey Doyno -- Fragments of devotion : charters and canons in Aquitaine, 876-1050 / Anna Trumbore Jones -- Naming names : the nomenclature of heresy in the early eleventh century / Thomas Head -- Economic development and demotic religiosity / Richard Landes -- Back-biting and self-promotion : the work of merchants of the Cairo Geniza / Jessica Goldberg -- John of Salisbury and the civic utility of religion / Mark Silk -- Understanding contagion : the contaminating effect of another's sin / Susan R. Kramer -- Calvin's smile / John Jeffries Martin -- Why all the fuss about the mind? : a medievalist's perspective on cognitive theory / Anne L. Clark -- Aspects of blood piety in a late-medieval English manuscript, London, British Library MS Additional 37049 / Marlene Villalobos Hennessy -- Machiavelli, trauma, and the scandal of the prince : an essay in speculative history / Alison K. Frazier -- Low country ascetics and oriental luxury : Jacques de Vitry, Marie of Oignies, and the treasures of Oignies / Sharon Farmer -- Crystalline wombs and pregnant hearts : the exuberant bodies of the Katharinenthal Visitation Group / Jacqueline E. Jung -- Gluttony and the anthropology of pain in Dante's Inferno and Purgatorio / Manuele Gragnolati -- "Human heaven" : John of Rupescissa's Alchemy at the end of the world / Leah DeVun -- Magic, bodies, university masters, and the invention of the late medieval witch / Steven P. Marrone -- Afterword : history in the comic mode / Rachel Fulton and Bruce Holsinger